Survey on the acceptance of patients with crush syndrome and the feasibility of implementing continuous renal replacement therapy at disaster base hospitals - Yada, Tetsuyasu; Ishii, Mieko; Uchiumi, Kiyono; Koido, Yuichi; Fujita, Retsu; Aluariachy, Larbi (Japanese Journal of Disaster Medicine, 2024)
【Purpose and Method】This study aimed to determine the current status and issues related to the acceptance of patients with crush syndrome and the ability to respond to blood purification therapy in the event of a major disaster at base hospitals for disaster management in Japan. 【Results】A questionnaire survey was conducted at 755 base hospitals for disasters in Japan. 256 institutions (34.0%) consented to the study, and 214 institutions (83.6%) provided valid responses. 【Discussion】It was clarified that 3,000 patients with crush syndrome, which is expected to occur in the northern Tokyo Bay earthquake, cannot be accepted.